Risk Perception and Preparedness of Undergraduate Dental Students to Treat Patients in View of COVID-19 Pandemic: A Questionnaire Survey - Anuprita Nair; Nishu Singla; Ritesh Singla; Arhana De (The Scientific World Journal)
With the gradual resumption of dental services worldwide, it is crucial to focus on returning dental undergraduates to their clinical postings. The assessment of foreseeable concerns from a student’s point of view will help the dental schools tailor a comprehensive plan of action that would be in the best interest of everyone. Aim. Hence, this survey was planned to assess dental undergraduates’ risk perception and preparedness to provide patient care amidst the COVID-19 pandemic crisis. Material and Methods. It was an online survey carried out among students involved in clinical work at two dental colleges in Manipal and Mangalore, respectively, in Karnataka, India. The online questionnaire was sent to approximately 500 students, with responses from 301 students. The survey comprised 21 closed-ended questions about demographics, risk perception, and preparedness. The descriptive statistics were done on the data. Results. It was found that all the students (99.7%) perceived COVID-19 to be dangerous, and 73.4% chose to avoid treating those patients suspected to have an active COVID-19 infection. The fear of being infected was perceived by 55.1% of students, while 46.2% feared transmitting the infection to friends and family. A majority (87.7%) believed standard infection controls practiced prior to the pandemic were insufficient to work in the current scenario. Nearly 33.6% could not view the guidelines for dental procedures during the pandemic. A majority (87.7%) were not/little confident, and 61.7% were unsure/unprepared to manage suspected patients. Conclusion. It is the prime need of the hour for dental schools to instill self-reliance within students in managing patient care under these circumstances by strictly reinforcing the official protective care guidelines.